2017
DOI: 10.3758/s13428-017-0966-7
|View full text |Cite
|
Sign up to set email alerts
|

The Box Task: A tool to design experiments for assessing visuospatial working memory

Abstract: The present paper describes the Box Task, a paradigm for the computerized assessment of visuospatial working memory. In this task, hidden objects have to be searched by opening closed boxes that are shown at different locations on the computer screen. The set size (i.e., number of boxes that must be searched) can be varied and different error scores can be computed that measure specific working memory processes (i.e., the number of within-search and between-search errors). The Box Task also has a developer's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Our findings resonate with a previous study which showed that AD patients are particularly impaired on the Box Task [9]. It is argued that the Box Task within-search error variable largely utilises visuospatial short-term store processes (i.e., visuospatial sketchpad [39]), whereas the between-search error variables measure additional memory loading processes, including binding/integrating objects and their location over trials (i.e., episodic buffer [39] and the active rehearsal of information over longer time periods (i.e., central executive [7,39]). The disproportionately high number of within-and between-search errors in the AD group is consistent with the commonly held view that multiple components of visuospatial working memory breakdown in typical AD, resulting in a particularly vulnerable visuospatial memory system [4,12,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings resonate with a previous study which showed that AD patients are particularly impaired on the Box Task [9]. It is argued that the Box Task within-search error variable largely utilises visuospatial short-term store processes (i.e., visuospatial sketchpad [39]), whereas the between-search error variables measure additional memory loading processes, including binding/integrating objects and their location over trials (i.e., episodic buffer [39] and the active rehearsal of information over longer time periods (i.e., central executive [7,39]). The disproportionately high number of within-and between-search errors in the AD group is consistent with the commonly held view that multiple components of visuospatial working memory breakdown in typical AD, resulting in a particularly vulnerable visuospatial memory system [4,12,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The Box Task is a computerised visuospatial working memory task in which pictures of closed boxes are presented at various locations, with increasing set sizes (4, 6 and 8 boxes) (Figure 1; see Kessels and Postma [7] for information on set up and administration of this task). Briefly, participants were instructed to find a hidden target object by 'opening' the boxes on the screen one by one.…”
Section: The Box Taskmentioning
confidence: 99%
See 3 more Smart Citations